Social norms and individual climate protection activities: A framed field experiment for Germany - Daniel Engler; Gunnar Gutsche; Amantia Simixhiu; Andreas Ziegler (Philipps-University Marburg, School of Business and Economics, 2022)
Based on the well-known observation that social norms can guide individual behavior, this paper empirically examines the causal effect of related information interventions on revealed climate protection activities, measured through incentivized donations. In our field-experi-mental setting, we differentiate between descriptive social norms by providing information about individual climate protection activities in Germany, injunctive social norms by provid-ing information about what people in Germany think about the need for climate protection activities, and a combination of both social norms. Based on representative survey data for more than 1,600 individuals in Germany, our econometric analysis shows some weak evi-dence that information about both descriptive and injunctive social norms increases donations for climate protection. The decomposition of this estimated average treatment effects reveals that the corresponding treatment particularly has a significantly positive effect at the extensive margin, i.e. on the probability to donate for climate protection. These results suggest that a combined information intervention referring to both descriptive and injunctive social norms is at least able to stimulate the general willingness for climate protection. In addition, our analysis of heterogeneous treatment effects reveals that strong social preferences (in terms of altruism and trust) and high environmental attitudes (in terms of environmental awareness and ecological policy identification) induce significantly positive information treatment effects on donations for climate protection. This result suggests that individuals in Germany with a strong environmental and social orientation do not only behave directly more climate-friendly, but can also be better stimulated by information about descriptive and/or injunctive social norms.
Keywords: Q54; D64; D83; D91; C93; 330; Climate protection activities; descriptive and injunctive social norms; information interventions; heterogeneous treatment effects; framed field experiment